Optimization Design of Mountain and Water Landscape of Traditional Mountain Village Based on New Robot Visual Technology - Xinxin Jia; Ruixin Liu; Zhi Qiao (Journal of Robotics)
The reasonable application of the random sampling consistent algorithm can be used to eliminate the theoretically possible error points and then complete the initial aiming pairing. The interior points obtained after this algorithm are used to estimate the relative adjacent poses of the new robot in the operation of the least squares method, so as to make certain improvements to the ICP (iterative closest point) algorithm, making it useful for accurate aiming pairing. Finally, by using the optimization method of G20, the posture of the new mobile robot relative to the adjacent position is optimized to a certain extent. In order to reasonably plan and design the landscape of mountain villages, this paper proposes the corresponding solution by analyzing the multidimensional value and landscape design data of traditional mountain villages, which not only needs to adapt to modern economic development but also needs to live in harmony with the natural ecological environment. Taking a village as a case for analysis, the village houses, roads, services, greening, ecology, and other aspects were reconstructed, and then, the detailed landscape design of the multimedia multidimensional resource village was analyzed and implemented.